Deny Golden Bear Report - Vallejo Times-Herald (Vallejo Times-Herald)
Reports of engine trouble on the Golden Bear, training ship of the California Maritime Academy, were deprecated yesterday by the Academy superintendent, Capt. H. E. Richter, USN, (Ret.).